سماوی مذاہب میں سزاؤں کے تصورات کا قرآن و سنت کی روشنی میں تحقیقی جائزہ : An Analytical Study of Punishment Concepts in Divine Religions: Insights from the Quran, Sunnah - Mubashir, Asadullah; Hussain, Taswar (Al-Amīr Research Journal for Islamic Studies, 2024)
In recent times, Islam has often been unfairly labeled as a religion that promotes fear and extremism due to its teachings on reward and punishment. However, such principles are not unique to Islam; they are also present in other major religions. Rather than spreading misunderstandings, it is essential to recognize the values within these beliefs that aim to build a just and peaceful society. This approach promotes unity among religions and helps reduce hatred and hostility. Islam has a unique, detailed, and well-organized system of justice based on reliable sources, especially the Quran, which has remained unchanged. In addition, the teachings of the Prophet Muhammad (ﷺ) serve as a secondary, verified source, providing a clear guide. Even teachings from the Torah and Bible are referenced to show shared moral values among religions. Justice has been a part of human history since ancient times, with each religion offering its own perspective. In Islam, personal freedom is respected but limited by divine rules to protect others’ rights. If these limits are crossed, certain punishments are outlined to restore peace and prevent harm. By following these principles, social order can be maintained, but ignoring them can lead to more problems. This study explores these ideas in three main sections to provide a clearer understanding. Keywords: Islam, reward and punishment, justice system, interfaith harmony, Quran, Hadith, ethics, societal reform, religious unity, Abrahamic religions, social order.